B Cell Depletion With an Anti‐CD20 Antibody Enhances Alloreactive Memory T Cell Responses After Transplantation. Issue 2 (9th November 2015) - Marino, J.; Paster, J. T.; Trowell, A.; Maxwell, L.; Briggs, K. H.; Crosby Bertorini, P.; Benichou, G.
Abstract : Alloreactive memory T cells mediate accelerated allograft rejection and transplant tolerance resistance. Recent studies have shown that B cell deficient–μMT mice fail to mount donor‐specific memory T cell responses after transplantation. At the same time, other studies showed that pretransplant B cell depletion using rituximab (IgG1 anti‐CD20 mAb) combined with cyclosporine A promoted the survival of islet allografts in monkeys. In this study, we investigated the effect of anti‐CD20 antibody‐mediated B cell depletion on the memory T cell alloresponse in mice. Wild‐type and anti‐OVA TCR transgenic mice were treated with an IgG2a anti‐CD20 monoclonal antibody, which depleted nearly all B cells in the peripheral blood and secondary lymphoid organs but spared some B cells in the bone marrow. B cell depletion did not affect the direct alloresponse but resulted in a marked increase of indirect alloresponse after skin transplantation of naïve mice. Furthermore, in allosensitized mice, anti‐CD20 mAb treatment enhanced the reactivation of allospecific memory T cells and accelerated second set rejection of skin allografts. This suggests that the effect of anti‐CD20 antibodies on alloimmunity and allograft rejection might vary upon the nature of the antibodies as well as the circumstances under which they are delivered.